(untitled) (Encuentros, 2022)
This article has to present the analysis of the disciplinary trend in physical education based on two discussion topics: object of study and purposes. This analysis was based on the methodological proposal of the qualitative paradigm, hermeneutical historical approach, and ethnographic method, and as information gathering techniques: the documentary review and the semi-structured interview. The findings elucidate that this trend has corporeality as its object of study and has, among other purposes, to promote an emancipatory physical education and concludes that said trend is far from the traditional positivist precepts to reach and weave new ways of approaching the problem of how to produce knowledge, from where and for whom, all this to build a physical education that helps to overcome the conditions of injustice and inequality and recognizes other knowledge and methodologies of an emancipatory nature that is shown to be absent.